The Hypoglycaemic Activity of Mengkudu (Morinda Citrifolia) - Chee, Beng Jin (2001)
Diabetes mellitus has existed for at least 2000 years and has been treated with materials derived from plants in many cultures of the world. The mengkudu (Morinda citrifolia) are known for countless medicinal values and the ripe fruits were being used traditionally in Malaysia for the treatment for diabetes mellitus. This study was carried out to verify the hypoglycaemic property and its possible effect on insulin secretion. Freeze-dried aqueous extracts of various doses of 3 mg/lkg, 30 mg/kg and 300 mg/kg were administered to normal rats in an acute effect study and the doses of 3 mg/kg, 30 mg/kg, 300 mg/kg, 600 mg/kg, 900 mg/kg and 1200 mg/kg were administered to streptozotocin induced type 2 diabetic rats in a chronic effect study in an Oral Glucose Tolerance Test (OGTI). Results from the choric effect study showed that the 300 mg/kg dose treated rats had an apparent hypoglycaemic effect as evident from the blood glucose level measured as the area under the OGTT curve (AUC: 4370.70 ± 99.13 mg%min) after 6 weeks of oral administration. Hypoglycaemic activity was also observed in the 600 mg/kg dose after 5 weeks of oral administration (AUC: 4486.70 ± 35.60 mg%min), the 900 mg/kg dose after 4 weeks of oral administration (AUC: 4340.40 ± 72.90 mg%min) and the 1200mglkg dose after 4 weeks of oral administration (AUC: 4554.00 ± 49.80 mg%min). All the Ave values were significantly lower compared to control. The aqueous extracts were also able' to impede the rate of glucose increase and enhance the glucose clearance. However, the results from the insulin assay did not show any significant change in the insulin release profile as compared to control. As a conclusion, the aqueous extract of mengkudu (Morinda citrifolia) fruit preparations in the doses of 300mglkg, 600mg/kg, 900mg/kg and 1200 mg/kg might contain plant compounds that have substantial hypoglycemic property only in the chronic effect study but did not affect the insulin secretion in the type 2 diabetic rats. Future studies should be carried out in order to further discover its mechanisms of action, isolation and identification of the hypoglycaemic components particularly with regard to the healing of diabetes by means of plant resources.